ANALISIS PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DI KANTOR LPP RRI PONTIANAK - Maksum; Yuliana (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2023)
This research was conducted with the aim of testing and analyzing the influence of the Leadership Style of the Consideration and Initiating Structure on Employee Performance with Job Satisfaction as a mediating variable in the LPP RRI Pontianak Office. This type of research is a survey using a quantitative approach. The population in this study were employees who worked in the LPP RRI Pontianak office with 60 respondents as the sample under study. The technique used is nonprobability sampling is a sampling technique that does not provide equal opportunities for each element or member of the population to be selected as samples and uses the purposive sampling method. The research variables are Leadership Style Consideration and Initiating Structure as independent variables while Employee Performance as the dependent variable. The data analysis method used by researchers is regression analysis using SPSS Version 18 The results of this study indicate that the variable that the Consideration leadership style has a positive impact on employee performance with a level of 95%. And the initiating structure leadership style has a positive effect on employee performance with a level of 95%. Then the variable of leadership style considering and initiating structure together has a positive effect on employee performance with a contribution of 57.7%,